184k views
5 votes
Help me with this question please‼️‼️

Help me with this question please‼️‼️-example-1
User Bardzusny
by
5.6k points

2 Answers

3 votes

Answer:

One way to find the gradient is using the expression :


m = (y_(2) - y_(1))/(x_(2) - x_(1)) = (y_(B) - y_(A))/(x_(B) - x_(A))

So
m = (6 - 1)/(6- (-4)) =(5)/(10) =(1)/(2)

User Starlocke
by
5.7k points
1 vote

Answer: 1/2 (choice C)

Step-by-step explanation:

The gradient is the same as the slope

m = slope

m = rise/run

m = (change in y)/(change in x)

m = (y2-y1)/(x2-x1)

m = (6-1)/(6 - (-4))

m = (6-1)/(6+4)

m = 5/10

m = 1/2

In decimal form, this becomes 0.5

A slope of 1/2 means we move up 1 and to the right 2 units each time to generate points along the diagonal line.

A positive slope goes uphill as we move to the right (due to the positive rise value).

User Scott Kramer
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.